FINANCIAL PERFORMANCE ANALYSIS OF STATE OWNED AND PRIVATE ENTERPRISES IN PHARMACEUTICAL INDUSTY LISTED IN INDONESIA STOCK EXCHANGE IN PERIOD YEAR 2012 - 2016 - Banani, Ade; Riyasari, Indah; Widiastuti, Ekaningtyas (Penerbit Atma Jaya Catholic University of Indonesia, 2019)
This study compares the financial performance between state owned and private enterprises in the pharmaceutical sub sector. The proxies for ratio analysis are current ratio, return on equity, debt equity ratio, and total asset turnover. By using independent sample t-test, the result shows that there was no significant difference between the financial performance of state owned and private enterprises on profitability ratio and activity ratio. Meanwhile, there was significant difference in the financial performance of state owned and private enterprises for liquidity ratio and leverage ratios. In addition, the result of the analysis illustrates that the performance of state owned enterprises were better than private enterprises in the  pharmaceutical sub sector.